2018
DOI: 10.1140/epjp/i2018-11852-0
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of Klein-Gordon particles in the background of mixed scalar-vector generalized symmetric Woods-Saxon potential

Abstract: Recently, it has been shown that the generalized symmetric Woods-Saxon potential energy, in which surface interaction terms are taken into account, describes the physical processes better than the standard form. Therefore in this study, we investigate the scattering of Klein-Gordon particles in the presence of both generalized symmetric Woods-Saxon vector and scalar potential. In one spatial dimension we obtain the solutions in terms of hypergeometric functions for spin symmetric or pseudo-spin symmetric cases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…2. One of the authors of this study, BCL, in a study published in 2018, examined the generalized symmetric Woods-Saxon potential energy with a constant mass term in the KG equation and showed that an energy spectrum at the EMOS limit cannot be obtained [42]. The results obtained in this study are in agreement with the results given by BCL.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…2. One of the authors of this study, BCL, in a study published in 2018, examined the generalized symmetric Woods-Saxon potential energy with a constant mass term in the KG equation and showed that an energy spectrum at the EMOS limit cannot be obtained [42]. The results obtained in this study are in agreement with the results given by BCL.…”
Section: Resultssupporting
confidence: 85%
“…Among a large number of articles, we would like to underline the investigations that employ Woods-Saxon [6], Hulthén [7], Morse [8], Rosen-Morse [9] , Eckart [10], Manning-Rosen [11], Pöschl-Teller [12], Kratzer [13], Hylleraas [14], multiparameter [15], exponential-type molecule [16], pseudoharmonic oscillator [17], Hartmann [18], double ring-shaped oscillator [19] potential energies.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we consider the Coulomb potential V (r) = − Ze 2 r and intend to derive a solution in three dimensional Dunkl-Klein-Gordon equation. We start by expressing the stationary Dunkl-Klein-Gordon equation according to [36]…”
Section: Coulomb Potentialmentioning
confidence: 99%
“…The Nikiforov-Uvarov method [8], factorization method [9], Laplace transform approach [10], and the path integral method [11] and shifted 1/N expansion approach [12,13] are used for solving radial and azimuthal parts of the wave equations exactly or quasiexactly in l ≠ 0 for various potentials. Additionally, there are numerous interesting research works about the KFG equation with physical potentials by using different methods in the literature [14][15][16][17][18][19][20][21][22][23][24][25][26]. Among them, as an example, in Ref.…”
Section: Introductionmentioning
confidence: 99%